2020
DOI: 10.1371/journal.pbio.3000755
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of human full-length kindlin-3 homotrimer in an auto-inhibited state

Abstract: Kindlin-1,-2, and-3 directly bind integrin β cytoplasmic tails to regulate integrin activation and signaling. Despite their functional significance and links to several diseases, structural information on full-length kindlin proteins remains unknown. Here, we report the crystal structure of human full-length kindlin-3, which reveals a novel homotrimer state. Unlike kindlin-3 monomer, which is the major population in insect and mammalian cell expression systems, kindlin-3 trimer does not bind integrin β cytopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(50 citation statements)
references
References 47 publications
4
46
0
Order By: Relevance
“…Notwithstanding, Kindlin-3 recruitment to CD18 temporally precedes the high affinity conformation of β 2 integrins ( 59 ). Additionally, structure function analyses have indicated that the pleckstrin homology domain of the F2 subdomain of the FERM domain is important for binding phosphatidylinositols at the plasma membrane ( 119 , 120 ), and that part of this protein population has been suggested to reside in an auto-inhibitory homotrimer ( 67 ). Moreover, high chemokine concentrations induce neutrophil arrest, which is mediated through high-affinity β 2 integrin by Kindlin-3 associating with the cytoplasmic tail of the β 2 subunit and PIP 3 increments upon strong activity of PI3K ( Figure 1B ) ( 104 ).…”
Section: Inside-out Signaling During Endothelial Transmigrationmentioning
confidence: 99%
See 2 more Smart Citations
“…Notwithstanding, Kindlin-3 recruitment to CD18 temporally precedes the high affinity conformation of β 2 integrins ( 59 ). Additionally, structure function analyses have indicated that the pleckstrin homology domain of the F2 subdomain of the FERM domain is important for binding phosphatidylinositols at the plasma membrane ( 119 , 120 ), and that part of this protein population has been suggested to reside in an auto-inhibitory homotrimer ( 67 ). Moreover, high chemokine concentrations induce neutrophil arrest, which is mediated through high-affinity β 2 integrin by Kindlin-3 associating with the cytoplasmic tail of the β 2 subunit and PIP 3 increments upon strong activity of PI3K ( Figure 1B ) ( 104 ).…”
Section: Inside-out Signaling During Endothelial Transmigrationmentioning
confidence: 99%
“…Notably, this motive is absent next to the second NXXY motif of other β integrins and could be a specific target for β 2 integrins ( 242 ), thus avoiding bleeding, a side effect also seen in LAD-III patients. Recent work has also elucidated for the first time the crystal structure of Kindlin-3 ( 67 ), which might partially reside as an auto-inhibitory homotrimer. Relaxation or enforcement of this homotrimeric state might be another way in which inside-out signaling can be influenced either positively or negatively, respectively.…”
Section: Therapeutic Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in sharp contrast, the crystal structure of full‐length kindlin‐3 solved by Bu et al revealed an auto‐inhibitory homotrimer where the integrin binding site on F3 domain of one molecule is masked by the PH domain of another (Figure 3(b)). 102 The authors also provided evidence to show that disruption of the trimer interface promotes integrin‐mediated cell adhesion and spreading 102 . Moreover, Kadry et al in a recent study suggested that both kindlin‐2 and kindlin‐3 can self‐associate into 2–4 molecule oligomers via their F2PH domains but with an interface different from that in the truncated kindlin‐2 dimer 103 .…”
Section: Kindlins and Kindlin Networkmentioning
confidence: 99%
“…Crystal structures of kindlins, including their complex with integrin β CT have been reported [ 52 , 53 , 54 , 55 ]. These studies have suggested that kindlins can multimerize.…”
Section: Introductionmentioning
confidence: 99%